2015
DOI: 10.1590/s0102-865020150110000006
|View full text |Cite
|
Sign up to set email alerts
|

Remifentanil protects uterus against ischemia-reperfusion injury in rats

Abstract: PURPOSE:To investigate the effects of remifentanil as an antioxidant and analyze the histopathologic, biochemical changes in experimental ischemia-reperfusion (I/R) exposed rat uteri. METHODS:Wistar albino rats were assigned to three groups (n = 7). 2h period of ischemia was followed by 1h of reperfusion in the I/R and the I/R-remifentanil groups. After ischemia, no drug was administered in the sham and I/R groups. In the I/R-remifentanil group, remifentanil infusion (2 μg/kg/min) was started in the ischemia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Hepatic I/R injury after transplantation or surgery is a major reason of liver failure. In recent years, remifentanil has gained increasing attention as a protective agent against I/R‐induced injury in liver, intestine, uterus, heart and other organs 5,34,42‐45 . However, the underlying mechanism of this effect remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic I/R injury after transplantation or surgery is a major reason of liver failure. In recent years, remifentanil has gained increasing attention as a protective agent against I/R‐induced injury in liver, intestine, uterus, heart and other organs 5,34,42‐45 . However, the underlying mechanism of this effect remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of this investigation, the average tourniquet duration was 51.56 ± 14.12 minutes, with extremes of 30 and 88 minutes. Apart from myocardial ischemia, which is usually established in less than an hour [1] [2] [8], in the majority of studies concerning the phenomena of tissue ischemia in general, and more specifically that of origin these lesions occur downstream and beyond the 2 nd hour during a circulatory interruption upstream [7] [51]. In other words, the duration of tourniquet less than 90 minutes could also be a factor explaining the absence of significant variation in plasma marker levels between groups of women M + G + and M + G −, despite their elevation within each of the two groups.…”
Section: Comparison Of Plasma Concentrations Of Gpx Cpk Ca 2+ K +mentioning
confidence: 99%
“…The name ischemia-reperfusion (I/R or IR) recalls that tissue damage is a direct result of hypoxia-ischemia and indirectly reperfusion-reoxygenation [6] [7] [8] [9]. Outside medical situations [1] [2] [9] [10] [11], certain types of surgeries are providers of I/R phenomena [1] [12]- [17], this is the case of the use of the tourniquet during myomectomy [17] [18] [19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…As there are reports suggesting the effectiveness of continuous infusion of remifentanil as much as pre-/post-conditioning with it, we also preferred to infuse remifentanil, following anesthesia induction 38. In a clinical study performed in uterine I/R injury, the authors demonstrated remifentanil’s activity in reduction of histopathological lesions and oxidative stress markers 39. This is probably due to the opioid-binding sites in rat kidneys.…”
Section: Discussionmentioning
confidence: 99%